Teaching Strategies : A guide to effective instruction - Orlich, Donald C.; Harder, Robert J.; Callahan, Richard C.; Trevisan, Michael S.; Brown, Abbie H.; Miller, Darcy E. (Wadsworth, USA : Cengage Learning, 2013)
TEACHING STRATEGIES, 10E, International Edition now in its tenth edition, is known for its practical, applied help with commonly used classroom teaching strategies and tactics. Ideal for anyone studying education or involved in a site-based teacher education program, the book focuses on topics such as lesson planning, questioning, and small-group and cooperative-learning strategies. The new edition maintains the book's solid coverage, while incorporating new and expanded material on InTASC standards, a new chapter on teaching in the inclusive classroom, and an up-to-date discussion of assessment as it relates to inclusion. The text continues to be supported by a rich media package anchored by TeachSource Video Cases, which bring text content to life in actual classroom situations.
Includes bibliographical references and index.
Keywords: Teaching -- Handbooks, manuals, etc; Lesson planning -- Handbooks, manuals, etc; Classroom management -- Handbooks, manuals, etc; Educational tests and measurements -- Handbooks, manuals, etc